The Effect of Scavenger Hunt Game on Students’ Reading Comprehension of Descriptive Text - Mike Amelia; Nostalgianti Citra Prystiananta (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research had purpose to find out whether there was a positive effect of scavenger hunt technique on students’ reading comprehension of descriptive text. Scavenger Hunt is a fact-finding and information-processing activity, where the students work in group to search for hidden items and perform task by using some clues.The method used in this research was quasi-experimental research. This research was conducted at the eighth grade students of SMP N 2 Kota Solok. The samples of this research were two homogeneous classes that chosen by using purposive sampling technique. The experimental class was taught by using scavenger hunt technique, meanwhile the control class was taught by using three phase technique. The technique of gathering the data of this research was by using reading test. The result of this research showed that there was a positive effect of implementation scavenger hunt technique, where the mean score at experimental class was 77,14 and control class was 72,94. Thus, the experimental students outcomes were higher than the control class.It means that students’ reading comprehension of descriptive text taught by using Scavenger Hunt game technique was better than taught by using three phase technique. Keywords: Scavenger Hunt, Reading Comprehension, Descriptive Text